Measurement properties of pain scoring instruments in farm animals: A systematic review using the COSMIN checklist - Tomacheuski, Rubia Mitalli [UNESP]; Monteiro, Beatriz Paglerani; Evangelista, Marina Cayetano; Luna, Stelio Pacca Loureiro [UNESP]; Steagall, Paulo Vinícius [UNESP] (Public Library of Science (PLoS), 2023)
This systematic review aimed to investigate the measurement properties of pain scoring instruments in farm animals. According to the PRISMA guidelines, a registered report protocol was previously published in this journal. Studies reporting the development and validation of acute and chronic pain scoring instruments based on behavioral and/or facial expressions of farm animals were searched. Data extraction and assessment were performed individually by two investigators using the Consensus-based Standards for the Selection of Health Measurement Instruments (COSMIN) guidelines. Nine categories were assessed: two for scale development (general design requirements and development, and content validity and comprehensibility) and seven for measurement properties (internal consistency, reliability, measurement error, criterion and construct validity, responsiveness and cross-cultural validity). The overall strength of evidence (high, moderate, low, or very low) of each instrument was scored based on methodological quality, number of studies and studies’ findings. Twenty instruments for three species (bovine, ovine and swine) were included. There was considerable variability concerning their development and measurement properties. Three behavior-based instruments scored high for strength of evidence: UCAPS (Unesp-Botucatu Unidimensional Composite Pain Scale for assessing postoperative pain in cattle), USAPS (Unesp-Botucatu Sheep Acute Composite Pain Scale) and UPAPS (Unesp-Botucatu Pig Composite Acute Pain Scale). Four instruments scored moderate for strength of evidence: MPSS (Multidimensional Pain Scoring System for bovine), SPFES (Sheep Pain Facial Expression Scale), LGS (Lamb Grimace Scale) and PGS-B (Piglet Grimace Scale-B). Most instruments (n = 13) scored low or very low for final overall evidence. Construct validity was the most reported measurement property followed by criterion validity and reliability. Instruments with reported validation are urgently required for pain assessment of buffalos, goats, camelids and avian species.